Career Flexibility- As a Response to the Impact of COVID 19 Pandemic - Chifamba, Constance (An Overview of Literature, Language and Education Research Vol. 5, 2024)
The purpose of this study was to investigate the impact of the Covid-19 Pandemic on the employment status of university graduates. A survey was carried out on University graduates to analyze the employment status of youth based on the skills they acquired at the University. Results indicated that the majority of the respondents are not formally employed, or those employed are not engaged in the jobs they trained for. Consequently, a high level of skills mismatch leads to skills obsolescence. In addition, most of the research participants indicated that they are engaged in hybrid jobs, mainly technical jobs to cope with the prevailing conditions. Postgraduates may need to consider retooling and upscaling the skills they initially trained for, develop career flexibility through trying new careers, and entrepreneurial skills, develop resilience (the ability to bounce back even after being retrenched), and acquire more digital Skills [1]. In conclusion, graduates need to be flexible and ready to venture into new areas as well as upscale to avoid skills obsolescence. The study recommends that young people need to be encouraged to train in multiple disciplines and develop career flexibility and competitive advantage to remain on the cutting edge.